Bacterial outer membrane vesicles as a candidate tumor vaccine platform - Wang, Shuming; Guo, Jiayi; Bai, Yang; Sun, Cai; Wu, Yanhao; Liu, Zhe; Liu, Xiaofei; Wang, Yanfeng; Wang, Zhigang; Zhang, Yongmin; Hao, Huifang (Frontiers in Immunology, 2022)
Cancer represents a serious concern for human life and health. Due to drug resistance and the easy metastasis of tumors, there is urgent need to develop new cancer treatment methods beyond the traditional radiotherapy, chemotherapy, and surgery. Bacterial outer membrane vesicles (OMVs) are a type of double-membrane vesicle secreted by Gram-negative bacteria in the process of growth and life, and play extremely important roles in the survival and invasion of those bacteria. In particular, OMVs contain a large number of immunogenic components associated with their parent bacterium, which can be used as vaccines, adjuvants, and vectors to treat diseases, especially in presenting tumor antigens or targeted therapy with small-molecule drugs. Some OMV-based vaccines are already on the market and have demonstrated good therapeutic effect on the corresponding diseases. OMV-based vaccines for cancer are also being studied, and some are already in clinical trials. This paper reviews bacterial outer membrane vesicles, their interaction with host cells, and their applications in tumor vaccines.